Modelling of Rhode Island Red chicken strains - KAUSAR, HINA; VERMA, MED RAM; KUMAR, SANJEEV; SHARMA, VIJAY BAHADUR; DAS, ANANTA KUMAR; DILLIWAR, LEENA (The Indian Journal of Animal Sciences, 2016)
To study the growth pattern in body weight of 3 strains of Rhode Island Red chicken Bertalanffy, gompertz and logistic nonlinear models were fitted. From the data on body weights of three strains of Rhode Island Red, we observed that average body weights of male chicken were higher than the female chicken. Based on the various measures of goodness fit criteria we have observed that in modelling of body weight of the Rhode Island Red chicken Bertalanffy was the best fitted model. In case of Rhode Island Control, Bertalanffy was the best fitted model and for Rhode Island Control male chicken logistic was the best fitted model. In case of Rhode Island White chicken logistic was the best fitted model and in case of Rhode Island White male chicken Bertalanffy was the best fitted model. In case of female chicken of Rhode Island Red, Rhode Island Control and Rhode Island White strains gompertz model was the best fitted model. From these fitted models one can determine the expected average body weight of a group of birds of three strains of RIR chicken at any given age under normal conditions.